2017
DOI: 10.15740/has/ajbs/12.2/202-208
|View full text |Cite
|
Sign up to set email alerts
|

Bioefficacy and dissipation studies of spiromesifen against mite, Polyphagotarsonemus latus banks on capsicum under field conditions

Abstract: Field experiments were conducted during 2013-14 and 2014-15 to evaluate the new insecticides for the management of mite, Polyphagotarsonemus latus banks and dissipation of effective insecticide on capsicum. Among the seven insecticides, mean of two seasons under poly house condition, population was less with spiromesifen (0.06 mites/ leaf) followed by diafenthiuron (2.21 mites/ leaf), triazophos (3.68 mites/ leaf) and thiamethoxam (5.30 mites/ leaf) which were significantly superior over untreated check (11.33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…However, in contradiction to our investigation, Sushil et al (2018) observed longer persistence of spiromesifen residues on T A B L E 2 Recovery of spiromesifen from fortified okra, chilli, capsicum and brinjal fruits at various spiked levels (n = 5) hot pepper that declined below the detectable level of 0.05 mg/kg on day 20 in comparison with 10 days in our investigation. In capsicum, Pathipati et al (2017) observed initial spiromesifen deposits of 1.29 mg/kg at 125 g a.i./ha that declined below the limit of determination at day 7 after spraying. Vinothkumar et al (2018) reported 0.715 and 1.123 mg/kg initial deposits in brinjal in support of our finding of an LOQ of <0.05 mg/kg on day 7.…”
Section: Analysis Of Residues In Okra Chilli Capsicum and Brinjalmentioning
confidence: 95%
See 2 more Smart Citations
“…However, in contradiction to our investigation, Sushil et al (2018) observed longer persistence of spiromesifen residues on T A B L E 2 Recovery of spiromesifen from fortified okra, chilli, capsicum and brinjal fruits at various spiked levels (n = 5) hot pepper that declined below the detectable level of 0.05 mg/kg on day 20 in comparison with 10 days in our investigation. In capsicum, Pathipati et al (2017) observed initial spiromesifen deposits of 1.29 mg/kg at 125 g a.i./ha that declined below the limit of determination at day 7 after spraying. Vinothkumar et al (2018) reported 0.715 and 1.123 mg/kg initial deposits in brinjal in support of our finding of an LOQ of <0.05 mg/kg on day 7.…”
Section: Analysis Of Residues In Okra Chilli Capsicum and Brinjalmentioning
confidence: 95%
“…As evident from the residue data, the half-life of spiromesifen was worked out as 1.6, 1.8, 1.9 and 1.7 days in okra, chilli, capsicum and brinjal, respectively, in our results. Various researchers have indicated the half-life degradation of spiromesifen on different crops to be 1.68 days in okra (Raj et al, 2012), 2-2.5 days in chilli at various locations Sharma, Dubey, et al (2007a), 2.62 days in hot pepper (Varghese et al, 2011), 2.09 days in capsicum at an application rate of 125 g a.i./ha (Pathipati et al, 2017), 2-3 days in brinjal (Sharma et al, 2006), 5-6 days in apple and 5-8.5 days in tea (Sharma et al, 2005;Sharma et al, 2006).…”
Section: Dissipation Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The half-lives of spiromesifen at the single and double prescribed doses were 3.65 and 3.19 days, respectively, and the corresponding waiting periods were 0.74 and 4.49 days. Pathipati et al (2017) studied the dissipation pattern of spiromesifen on capsicum and found initial deposits of 1.29 mg kg À1 . Spiromesifen reached the below detectable level (BDL) in 7.0 days and the waiting period worked out for the safe harvest of capsicum was 7.0 days, which strongly supported the present findings.…”
Section: Dissipation and Persistence Studymentioning
confidence: 99%
“…Pesticide residues in food and their penetration into the food chain have sparked extensive public discussion. Few dissipation studies were performed to generate data on the effects of spiromesifen insecticides on chili fruits (Pathipati et al, 2017; Sharma, Rao, et al, 2007; Sushil et al, 2018; Varghese et al, 2011; VinothKumar, 2020; Viswanathan & Paul, 2020; Xavier & Chandran, 2016). Herein we report the dissipation kinetics and risk assessment of the effect of spiromesifen on chili fruits.…”
Section: Introductionmentioning
confidence: 99%